2002
DOI: 10.1080/10258140290027234
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance Of M r 25,000 Protein, a New Protein Kinase Substrate, in Parallel with a kind of Serpin During Embryogenesis

Abstract: M(r) 25,000 protein (pp25) is a protein kinase substrate detected recently in Xenopus laevis oocytes [Hashimoto, E. et al. (1995) J. Biochem. 118, 453-460], but the physiological role of this protein remains to be determined. In order to elucidate some characteristics of pp25, a polyclonal antibody was raised against it and the distribution and quantitative changes of this protein were examined using various tissues and biological systems. In Western blot analysis, pp25 was detected only in Xenopus oocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, it is not known whether they function only as nutrient sources. In a previous report (Funami et al 2002), we showed that the level of pp25 did not change markedly until stage 40 of early embryogenesis, and that pp25 disappeared completely after stage 48. If pp25 exists in the cytosol only as a nutrient source in a non-crystallized form, it seems somewhat surprising that pp25 disappeared suddenly during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is not known whether they function only as nutrient sources. In a previous report (Funami et al 2002), we showed that the level of pp25 did not change markedly until stage 40 of early embryogenesis, and that pp25 disappeared completely after stage 48. If pp25 exists in the cytosol only as a nutrient source in a non-crystallized form, it seems somewhat surprising that pp25 disappeared suddenly during embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with these experiments, we also examined the expression pattern of putative vitellogenin B1 protein in female tissues using pp25-specific antibody. In a previous study, we detected pp25 in the ovary but not in other tissues (Funami et al 2002). However, a larger protein with Mr of approximately 220 000, probably corresponding to vitellogenin B1, was detected in all of the organs examined (Fig.…”
Section: Tissue-specific Expression Of Vitellogenin B1mentioning
confidence: 99%
See 3 more Smart Citations